Power oscillation damping control by satcom using fuzzy controller - Ravikumar, N.; Krishnan, S.; Yokeshkumar, B. (AIP conference proceedings, 2022)
The plan of a significant force wavering damping (POD) regulator for a static coordinated compensator is the subject of this paper (STATCOM). This is cultivated by utilizing a fluffy regulator, which empowers the estimation of low-recurrence electromechanical motions from privately estimated signals even with power framework unsettling influences in a quick, particular, and versatile way. The proposed strategy functions admirably for expanding framework damping at the frequencies of premium, just as within sight of framework boundary vulnerabilities and at various compensator interface focus. To start, a straightforward two- machine framework model will be utilized to look at the effect of dynamic and receptive force infusion into the force framework. The worked-on model will be utilized to build up a control methodology for improving dynamic and receptive force infusion at different STATCOM interface focuses. The proposed control technique will be exposed to a little flag investigation of its perplexing yield. Reenacted and trial results will be utilized to check the adequacy of the proposed control technique in giving force swaying damping, paying little mind to the gadget’s association point and within sight of framework boundary vulnerabilities.